Nitrogen deposition in forests: Statistical modeling of total deposition from throughfall loads - Braun, Sabine; Ahrends, Bernd; Alonso, Rocio; Augustin, Sabine; García-Gómez, Hector; Hůnová, Iva; Karlsson, Per Erik; Karlsson, Gunilla Pihl; Schmitz, Andreas; Thimonier, Anne (Frontiers in Forests and Global Change, 2022)
Introduction Nitrogen (N) gradient studies in some cases use N deposition in throughfall as measure of N deposition to forests. For evaluating critical loads of N, however, information on total N deposition is required, i.e., the sum of estimates of dry, wet and occult deposition. Methods The present paper collects a number of studies in Europe where throughfall and total N deposition were compared in different forest types. From this dataset a function was derived which allows to estimate total N deposition from throughfall N deposition. Results At low throughfall N deposition values, the proportion of canopy uptake is high and thus the underestimation of total deposition by throughfall N needs to be corrected. At throughfall N deposition values > 20 kg N ha–1 yr–1 canopy uptake is getting less important. Conclusion This work shows that throughfall clearly underestimates total deposition of nitrogen. With the present data set covering large parts of Europe it is possible to derive a critical load estimate from gradient studies using throughfall data.